The robotic mentalist – On the influences of robots’ mentalizing abilities and external manipulative intent on people’s credibility attributions - Finkel, Marcel; Krämer, Nicole C. (Frontiers in Psychology, 2022)
Robots are used in various social interactions that require them to be perceived as credible agents (e.g., as a product recommender in a shopping mall). To be rated credible (i.e., competent, trustworthy, and caring) a robot’s mentalizing abilities have shown to be beneficial because they allow a robot to infer users’ inner states, thus serving as a prerequisite for understanding their beliefs and attitudes. However, social robots are often deployed by private and thus profit-oriented companies. In such cases where an organization’s implied manipulative intent is salient, the effect of robots’ mentalizing abilities might be reversed. In this case, mentalizing abilities could pose a persuasive threat to users rather than a feature for better understanding, thereby decreasing credibility attributions. These assumptions were tested in a three (robot’s mentalizing abilities) by two (external manipulative intent) between-subjects, pre-registered, laboratory experiment during which participants interacted with a social robot that recommended experience vouchers as potential gifts for participants’ target persons. Contrary to our assumptions, inferential statistical results revealed no significant differences in explicit or indirect credibility attributions caused by the experimental manipulation. The external manipulative intent of an organization using the robot caused no differences in participants’ behavioral intentions or evaluations of it. Furthermore, only participants’ attribution of empathic understanding to the robot varied significantly between the three mentalizing conditions. Our results suggest that people focus more on the robot than on the organization using it, causing potential opportunities for such organizations to hide their economic interests from the users.